The Mediating Role of Brand Trust: Is Enhancing TikTok Marketing Activities Important to Create Loyalty? - Mettasari, Bewita; Kurniawati, Kurniawati; Masnita, Yolanda (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Indonesian people are becoming more aware of the significance of skincare, increasing the demand for beauty care products. As a result, the frequency of purchasing skincare products in Indonesia has also risen. Local Indonesian skincare is a popular choice among the public. The variety of local skincare products encourages competition among companies to market their products. In the times, marketing through social media is increasingly popular to interact directly with customers. Indonesia ranks second in the world, with the number of TikTok users reaching 109.90 million. This research uses the S-O-R Model to analyze the positive influence of Marketing Activities on social media on Brand Loyalty, with the mediating role of Customer Brand Engagement and Brand Trust. The hypothetical relationships in the proposed model are tested using Structural Equation Modeling (SEM). Of the total respondents who were TikTok users for six months or more, 87.3% were women. This research aims to understand how social media marketing activities (SMMA) impact brand loyalty (BLO) for local skincare brands in Indonesia. It also considers the mediating roles of customer-based equity (CBE) and brand trust (BTR) in this relationship. The results of hypothesis testing showed a significant positive influence on all variables tested. The role of mediation has also proved significant, albeit with varying degrees of influence. Some variables tend to have a low influence on Brand Loyalty, while the most significant influence is seen in the influence of SMMA on Brand Trust. Thus, this study has important implications for local skincare companies in developing effective marketing strategies to build strong brand loyalty and increase customer trust in the brand.